Collaboration in the arts for interdisciplinary practice at the Institut Kesenian Jakarta, Indonesia - Indah Tjahjawulan (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2021)
In recent years, the interdisciplinary approach to art has gained popularity in the field of art studies. Numerous art studies transcend creative disciplines, allowing for the production of novel ideas and works. This study aims to understand the multidisciplinary art and design processes at the Institut Kesenian Jakarta. The data were acquired by observation and a review of the literature. Observations were made in order to collect field data about the work of art. This observation method was employed while visiting numerous exhibitions and performances at the Institut Kesenian Jakarta, and the literature was sourced by reading articles published in foreign magazines. The examination focuses on the difficulty inherent in diverse art practices. This study discovered that collaborative work increases the process of knowledge exchange between members and groups. As a result, an art ecosystem is developed from the standpoint of art creation and study. This research contributes to the discovery of new creative models or value chains and the provision of fundamental knowledge to develop a diverse art ecosystem. Art colleges can also contribute to interdisciplinary understanding and culture by fostering knowledge and abilities in art creation that are applicable across fields and are not constrained by the nomenclature of a single 'subject of arts'